Studium vlivu studeného chmelení na stabilitu pivní pěny - Benda, David (Vysoké učení technické v Brně. Fakulta chemická, 2022)
Tato diplomová práce se zabývá vlivem studeného chmelení na stabilitu pivní pěny. Byl sledován vliv studeného chmelení na základní charakteristiky piva, obsah hořkých chmelových kyselin, proteinů, fenolických látek, vybraných mikro- a makroprvků, organických kyselin a stabilitu pivní pěny. V teoretické části jsou charakterizovány suroviny pro výrobu piva, látky ovlivňující stabilitu pivní pěny a postup přípravy piva. Dále je popsána pěna z fyzikálního hlediska, je popsán její vznik, odvodňování a jevy, které vedou k jejímu zániku. Blíže jsou popsány i použité analytické metody. Experimentální část popisuje postup přípravy modelového piva a realizaci studeného chmelení českou odrůdou Kazbek. Studené chmelení bylo provedeno v časech 3, 5 a 10 dní s navážkami 3 g/l a 6 g/l. Připravené pivo bylo následně analyzováno z hlediska základních pivních charakteristik, stability pivní pěny, hořkých chmelových kyselin, fenolických látek, proteinů, vybraných mikro- a makroprvků a organických kyselin. Z naměřených dat byly zjištěny korelace mezi sledovanými parametry piva a stabilitou pivní pěny. Bylo zjištěno, že studené chmelení v pivu zvyšuje obsah fenolických a hořkých látek, jeho vliv na stabilitu pivní pěny je ale negativní.

This diploma thesis deals with the influence of dry hopping on the stability of the beer foam. It was observed how this effect affected general characteristics of beer, the content of hop bitter acids, proteins, phenolic compounds, selected micro- and macro elements, organic acids and the stability od the beer foam. Theoretical part characterises raw the materials for beer production, the substances affecting the stability of beer foam and the beer brewing process. Furthermore the beer foam is described froam a physical point of view together with the steps of its formation and drainage as well as other phenomena that lead to its disappearance. A detailed description of used analytical methods is included. The experimental part illustrates the preparation of the model beer and the implementation of dry hopping with the Czech hop variety called Kazbek. Dry hopping was carried out on day 3, day 5 and day 10 with a 3 g/l and a 6 g/l hop dose. The prepared beer was subsequently analysed for general characteristics, the beer foam stability, bitter hop acids, phenolic compounds, protein, selected micro- and macroelements and organic acids. Based on the measured data, there were found correlations between the observed beer parameter and the stablity of the beer foam. The results revealed that dry hopping in beer increases the content of the phenolic compounds and bitter substances, but its effect on the beer foam stability is negative.
Effect of the dry hopping of the stability of beer foam
Keywords: Pivo; stabilita pivní pěny; chmel; studené chmelení; iso--kyseliny; proteiny; fenolické látky; ICP-OES; IC; UV-VIS; NIBEM; Beer; beer foam stability; hop; dry hopping; iso--acids; proteins; phenolic compounds; ICP OES; IC; UV-VIS; NIBEM